Controlling Malleability of Metamaterials through Programmable Memory. Issue 3 (30th July 2022) - Wenz, Franziska; Schönfeld, Dennis; Fischer, Sarah C. L.; Pretsch, Thorsten; Eberl, Christoph
Abstract : Malleability, the ability to adapt materials to specific shapes, is necessary in applications where a form closure is requested. The material should be easily deformable between desired stable shapes. Such stability can be obtained through bistable elements that act as memory in metamaterials. Herein, a material with memory behavior programmed by the local temperature is presented. The behavior can be switched between a permanent shape change and a complete elastic recovery after removing an applied mechanical load. Additionally, a deformed material can be forced to recover its shape by heating. Through an adaption of the mesostructure and the used polymers, the characteristic behavior (switching time and temperature) can be adjusted. Furthermore, heating can be applied locally that only certain parts are able to change. A unit cell design based on analytical and numerical analyses is demonstrated that considers not only the mesostructure but also the combination of polymeric materials with specific thermoresponsive mechanical behavior. Unit cells and structures of several cells are additively manufactured to validate the programmable behavior. The concept is extended to indirect heating with an alternating magnetic field, using a compound made from a polymeric material and magnetic particles. Abstract : A material with malleability programmed by the temperature is presented. The behavior can be switched between a permanent shape change and complete elastic recovery. A design based on analytical and numerical analyses is demonstrated that considers not only the mesostructure but also the combination of polymers with thermoresponsive and magnetoresponsive behavior.